Externally controllable glycan presentation on nanoparticle surfaces to modulate lectin recognition. Issue 2 (19th December 2016) - Won, Sangho; Richards, Sarah-Jane; Walker, Marc; Gibson, Matthew I.
Abstract : Response polymer gates are employed to enable external control of glycan expression on the surface of multivalent nanoparticles. Abstract : Nature dynamically controls carbohydrate expression on cells rather than static presentation. Here we report synthetic glycosylated nanoparticles that contain polymeric 'gates' to enable external control ( via temperature changes) of glycan surface expression, as an alternative to enzymatic control in nature. This approach offers a new dynamic multivalent scaffold for glycan recognition.